Inhibiting the detrimental Cu protrusion in Cu through-silicon-via by highly (111)-oriented nanotwinned Cu. (May 2021) - Lin, Ting-Chun; Liang, Chien-Lung; Wang, Shan-Bo; Lin, Yung-Sheng; Kao, Chin-Li; Tarng, David; Lin, Kwang-Lung
ABSTRACT: Cu protrusion phenomenon, one of the biggest challenges of the Cu through-silicon-via (TSV) technology, results from the thermal stress accumulation and the following plastic deformation during thermal annealing. Herein, we proposed an effective approach to inhibiting the detrimental Cu protrusion by introducing a highly (111)-oriented nanotwinned Cu to the TSV structure. The Cu nanotwin structure, in comparison with the normal Cu structure, gave rise to a 70.3% decrement of the protrusion height during thermal annealing at 250°C. The protrusion inhibition was attributed to the effective interaction of high-fraction coherent nanotwin boundaries with dislocations. The presence of low-energy coherent twin boundaries impeded dislocation glide, giving rise to the TSV strengthening and the significant protrusion inhibition. The electrodeposited nanotwinned Cu TSV exhibited great thermal stability under thermal annealing at 250°C for 2 h, as evidenced by the slight micro-hardness loss, 6.7%, based on the nanoindentation analysis. Graphical abstract: Image, graphical abstract